2016
DOI: 10.23863/kalem.2017.65
|View full text |Cite
|
Sign up to set email alerts
|

Ortaokul Öğrencilerinin Algıladıkları Sosyal Destek ile Motivasyon Yönelimleri Arasındaki İlişkinin Yapısal Eşitlik Modeli ile İncelenmesi

Abstract: The aim of this study was to analyze the predictor effect of the social support, perceived by students, on their motivational orientation. The subjects of the study consisted of 561 students that received education in Bartın during 2013-2014 education year and selected through an applicable sampling method. The Perceived Support Scale developed by Yıldırım (2004b) as well as the Scale of Motivational Orientations in the Classroom developed by Lepper, Corpus and Iyengar (2005), translated into Turkish by Tuluna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(26 reference statements)
0
0
0
1
Order By: Relevance
“…Therefore, it was found that income level does not significantly affect IA and PSS. However, other studies showed that there is significant difference between IA and PSS according to family income level (Ak et al, 2013;Tulunay-Ateş, 2016). As a result, it is thought that this study conducted on adolescents will clarify adolescents' IA and PSS levels.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 77%
“…Therefore, it was found that income level does not significantly affect IA and PSS. However, other studies showed that there is significant difference between IA and PSS according to family income level (Ak et al, 2013;Tulunay-Ateş, 2016). As a result, it is thought that this study conducted on adolescents will clarify adolescents' IA and PSS levels.…”
Section: Discussion Conclusion and Implicationsmentioning
confidence: 77%
“…Ortaokul öğrencilerinin algıladıkları sosyal desteğin içsel ve dışsal motivasyonu pozitif yönde yordadığı bulunmuştur (Tulunay-Ateş, 2016). Ayrıca, yine ortaokul çocuklarının dışsal motivasyonunun öğrenim düzeyine göre, içsel motivasyonunun ise cinsiyet, öğrenim ve akademik başarı düzeyine göre farklılaştığı bulunmuştur (Çolak ve Cırık, 2015).…”
Section: Yaratıcılık Motivasyon Ve öDülunclassified